A STUDY OF WORK LIFE BALANCES AMONG WOMEN EMPLOYEES IN THE BANKS OF THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Bank is a monetary foundation that acquires cash from people in general and loans one to public for gainful reason. The Indian financial Regulation demonstration of 1949 characterizes the term banking as " Accepting to loan all speculation of store ,of cash from public ,repayable, on interest or something else and withdrawal with a money order or something else, ".In the new occasions when the help business is achieving more noteworthy significance contrasted with assembling industry , banking has developed as an excellent area offering monetary assistance to developing need s of the economy. Banking area as of late has joined new items in their business ,Which are help full for development .The banks have begun to give expense based assistance like depository tasks ,overseeing subordinates ,alternative and prospects ,going about as a financier to the business during the public contribution ,giving consultancy administration ,going about as a middle person between two-business entities.etc. So the financial area ought to receive pressure the executives strategies.